Efficacy of high-flow nasal oxygenation compared with laryngeal mask airway in children undergoing ambulatory oral surgery under deep sedation: A randomized controlled non-inferiority trial - Ran, Longkuan; Huang, Guijin; Yao, Ying; Wu, Yujia; Zhang, Chao; Wang, Yan; Yu, Cong (Frontiers in Medicine, 2022)
ABSTRACT Background: High-flow nasal oxygenation (HFNO) has been suggested an alternative oxygenation method during procedural sedation. This randomized, non-inferiority trial evaluated the safety and efficacy of HFNO compared with LMA in pediatric ambulatory oral surgery under deep sedation. Methods: One hundred and twenty children aged 2 to 7 years old (10.0 to 30.0 kg) were equally assigned into 2 groups: HFNO with propofol total intravenous anesthesia infusion (HFNO-IV); or LMA with propofol total intravenous anesthesia infusion (LMA-IV). The primary outcome was carbon dioxide (CO2) accumulation during perioperative. Secondary endpoints included transcutaneous oxygen saturation, grade exposure to the surgical field, perioperative adverse events, or other events. The predefined noninferiority margin was 7 mmHg. During the COVID-19 pandemic, a novel WeChat applet was implemented to gather follow-up after discharge. Results: Noninferiority could be declared for HFNO relative to LMA (mean difference in TcCO2 = –1.4 mmHg, 95% CI: –2.9, 0.1 mmHg; P>0.05). The pre-surgical TcCO2 of the HFNO-IV group (45.4 ± 4.5 mmHg) was similar to that of the LMA-IV (44.0 ± 3.5 mmHg), within the clinically acceptable normal range. All the children maintained SpO2> 97%. The surgical field exposure score of the HFNO group was significantly better than that of the LMA group. There was no significant difference between the 2 groups regarding risk, or adverse events. Conclusions: HFNO was not inferior to LMA for maintaining oxygenation and ventilation in pediatric ambulatory oral surgery under deep sedation under strict isolation from oral cavity to upper airway.